Decoding sugarcane smut: the role of effector SsEF83 in fungal virulence and plant interaction - Huang, Xuecheng; Liu, Zongling; Su, Yizu; Qiu, Jinfeng; Wu, Haoming; Ming, Zhenhua; Li, Ru (Frontiers in Microbiology, 2025)
Sugarcane smut, caused by the fungus Sporisorium scitamineum, severely affects global sugarcane production. Effector proteins are crucial for fungal invasion and virulence in plants. Nevertheless, few studies have identified effector proteins in S. scitamineum and demonstrated their functions in smut progression. This study aimed to characterize SsEF83 (SPSC_06083), a cysteine-rich core effector of S. scitamineum. Our qRT-PCR results revealed that the expression of SsEF83 was significantly upregulated at 24, 72, and 168 h post-infection in sugarcane. Further confirmation of the secretion function of the SsEF83 signal peptide was provided by the yeast secretion system. SsEF83 was found to induce cell death in Nicotiana benthamiana leaves. Subcellular localization analysis indicated that SsEF83 protein was localized in the cytoplasm. Notably, the deletion of SsEF83 did not alter fungal morphology, growth, and mating/filamentous, but it significantly attenuated the virulence of S. scitamineum. Furthermore, yeast two-hybrid screening was employed to identify sugarcane proteins interacting with SsEF83. Five sugarcane proteins were found to interact with SsEF83, and these interactions were confirmed by Bimolecular Fluorescence Complementation (BiFC). Through AlphaFold 3 analysis of the interactions between SsEF83 and target proteins, significant binding interactions were detected between SsEF83 and target-2 or target-4. Moreover, our previous RNA-seq data suggested a potential association between the two target proteins and sugarcane's susceptibility or resistance to smut. Collectively, our findings demonstrated that the effector SsEF83 plays a crucial role in the virulence of S. scitamineum, providing new insights into the interaction between smut fungi and sugarcane.